2019
DOI: 10.1039/c9ta06947j
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur encapsulation by MOF-derived CoS2 embedded in carbon hosts for high-performance Li–S batteries

Abstract: The superior performance of S/ZIF-derived CoS2 embedded in a carbon framework originates from both physical confinement of sulfur inside the host and strong chemical interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 73 publications
0
49
0
1
Order By: Relevance
“…observed the distribution of S in various types of carbon/S composites through cryo‐STEM and demonstrated that uniform S infiltration and dispersion through the melt infusion method was easier in activated porous carbon hosts than in nonactivated porous carbon, hollow carbon spheres, and carbon nanotubes (Figure 7B). 62 …”
Section: Characterization Of Catalytic Mechanismmentioning
confidence: 99%
“…observed the distribution of S in various types of carbon/S composites through cryo‐STEM and demonstrated that uniform S infiltration and dispersion through the melt infusion method was easier in activated porous carbon hosts than in nonactivated porous carbon, hollow carbon spheres, and carbon nanotubes (Figure 7B). 62 …”
Section: Characterization Of Catalytic Mechanismmentioning
confidence: 99%
“…[11] A great number of efforts have been focused on improving the performance of diaphragm [12] and optimizing the cathode matrix to avoid the shuttle effect of PSs and improve the safety of batteries. [13][14][15] Ideal cathode materials could provide suitable space for the fixation of PSs, enhance the electrical conductivity of active substances and alleviate the volume expansion in discharge process. [16][17][18][19][20][21] In addition, the polar materials can efficiently anchor polysulfides [22][23][24] and the effective catalysts contribute to the redox conversion of them.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] However, the issues related to dissolution of polysulfide during charge and discharge are the main obstacles to the commercialization of LiÀ S batteries. [6][7][8][9] To solve these problems, many groups have focused on the application of porous carbons for LiÀ S batteries. Ever since Ji et al [10] demonstrated the potential of S/CMK-3 (obtained by the melt-diffusion method) for high-capacity applications, many researchers have focused on the fabrication of S/C composites.…”
Section: Enhancing the Of Performance Of Lithium-sulfur Batteries Thrmentioning
confidence: 99%